Comparison of effectiveness between two treatment methods for patients with anal fistula and their impact on serum IL-6 and SAA - Lu, Yi; Han, Yazhu; Cheng, Shichao; Zhang, Xin (Journal of the Pakistan Medical Association, 2025)
Objective: Observation of the clinical effect of Jiedu Shengji ointment in treating anal fistula and its impact on serum interleukin-6 and serum amyloid A. Methods: The clinical comparative study was conducted at Baoding No 1 Central Hospital, China, between January 2023 and February 2024, and comprised patients diagnosed with anal fistula who underwent surgery. The participants were randomly assigned to control group A which received dressing changes using Vaseline gauze, and intervention group B which was treated with Jiedu Shengji ointment in conjunction with Vaseline gauze. Treatment outcomes between the groups were compared. Data was analysed using SPSS 20. Results: Of the 60 patients, 30(50%) were in group A; 20(66.6%) men and 10(33.3%) women with mean age 32.56±2.66 years (range: 22-43 years). There were 30(50%) patients in group B; 22(73.3%) men and 8(26.7%) women with mean age 32.14±2.35 years (range: 22-42 years). Total effective rate of treatment in group B was 86.67% compared to 63.33% in group A (p<0.05). After 7 and 14 days of treatment, the levels of interleukin-6 and serum amyloid A in group B were significantly better than those in group A (p<0.05). The wound bleeding score, wound healing time, and wound oedema score of group B were significantly better than those of group A (p<0.05). After treatment, the visual analogue scale and the Faecal Incontinence Severity Index scores of group B were significantly better than those of group A (p<0.05). After treatment, the levels of transforming growth factor-Beta and epidermal growth factor in group B were significantly better than those in group A (p<0.05). Conclusion: Jiedu Shengji ointment demonstrated remarkable therapeutic efficacy in patients with surgical treatment for anal fistula. Key Words: Anal fistula, Jiedu Shengji ointment, Clinical efficacy, IL-6, SAA.